Application of Role Playing Methods to Improve Students' Language Skills - Rusminah, Siti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
There are still many elementary school students who have not been able to interact with good and correct language, especially Indonesian. So that in order to achieve the goals of learning Indonesian perfectly, it is expected that teachers in delivering teaching materials can choose and use learning methods that are appropriate to the material. This article is a literature study that discusses the use of role playing models in developing children's language. The method of role playing or role playing is the right one to achieve the perfection of Indonesian language learning objectives, namely to improve students' skills in language or communication. Through the role playing method students are required to play an active role in trying language skills with word processing and intonation according to their own abilities, students will understand very well what is being discussed and done. So that they can use Indonesian properly and correctly.